1970
DOI: 10.1136/bmj.2.5700.23
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effect of Salbutamol and Isoprenaline on Spirometry and Blood-gas Tensions in Bronchial Asthma

Abstract: Mothers adopting this method, however, were more inclined to clean the utensils better beforehand, and they stored them in solution, thus avoiding subsequent contamination.Undoubtedly, many factors are involved in achieving satisfactory results by either method-social class, educational level, mothercraft advice obtained, and so on. It may even be that (in the words of one of the doctors involved in the project) "a 'method of sterilization,' presumed to be based on chemistry, is followed more carefully and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…He therefore concluded that the addition of an a-adrenoceptor stimulating drug (phenylephrine) probably prevented the vasodilatation induced by isoprenaline and so prevented the fall in oxygen tension. It is of interest that in this study a rise in pulmonary artery pressure occurred only with salbutamol and that there was a minimal fall in arterial 02 tension with this drug; these findings agree with those of Palmer et al (1970) for salbutamol in bronchial asthma patients. As can be seen from Table 3, which combines the data of Finlay, Wightman & Sykes (1970) with our studies, all the above-mentioned changes are dose dependent.…”
Section: Respiratory Changessupporting
confidence: 86%
See 1 more Smart Citation
“…He therefore concluded that the addition of an a-adrenoceptor stimulating drug (phenylephrine) probably prevented the vasodilatation induced by isoprenaline and so prevented the fall in oxygen tension. It is of interest that in this study a rise in pulmonary artery pressure occurred only with salbutamol and that there was a minimal fall in arterial 02 tension with this drug; these findings agree with those of Palmer et al (1970) for salbutamol in bronchial asthma patients. As can be seen from Table 3, which combines the data of Finlay, Wightman & Sykes (1970) with our studies, all the above-mentioned changes are dose dependent.…”
Section: Respiratory Changessupporting
confidence: 86%
“…It has also been suggested that the increase in the number of deaths due to asthma may be associated with the more frequent use of isoprenaline inhalers Speizer, Doll, Heaf & Strang, 1968). A new potent bronchodilator, salbutamol, has been recently introduced (Brittain, Farmer, Jack, Martin & Simpson, 1968) which, it has been suggested, does not have a significant effect on the cardiovascular system and does not produce a fall in arterial oxygen tension (Palmer & Diament, 1969;Palmer, Legge, Hamilton & Diament, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…The significant decrease in arterial oxygen tension observed in this study during the infusion of dobutamine at 15 and 30 /ig kg" 1 min" 1 has also been shown during the infusion of dopamine to patients (Lemaire et al, 1976) and during the infusion of isoprenaline to dogs (Finlay, Wightman and Sykes, 1970) and to patients (Knudson and Constantine, Palmer and Diament, 1968;Palmer et al, 1970). However, unlike that of dopamine, the action of dobutamine does not appear to depend on the release of endogenous catecholamines (Bodem, Skelton and Sonnenblick, 1974) nor, as in the case of dopamine, is it likely to be further converted to another active form.…”
Section: Arterial Oxygen Tensionsupporting
confidence: 74%
“…Ten of 12 patients with chronic airways obstruction other than asthma who inhaled an unstated dose of salbutamol showed an average fall of 6.3 mm Hg. Palmer et al (1970) have compared the cardiovascular and respiratory effects (measured simultaneously) of aerosol inhalation of 0.2 mg salbutamol and 1 mg isoprenaline in the same 11 chronic asthmatic patients. In the other brief report, the Pa~fell (range 2.5 to 11 mm Hg) in 7 of 9 patients with emphysema following inhalation of 0.2 mg salbutamol ; P aC0 2 increased (range 2 to 10 mm Hg) in 6 of the 9 patients.…”
Section: Bronchodilator Activitymentioning
confidence: 99%